Collaborative Governance for Sustainable Tourism Development: Strategy Development and Reflections from the KEK Mandalika Case Study, Indonesia - Lalu Hanjayadi Imran; Sakir Ridho Wijaya (Journal of Government and Politics (JGOP), 2025)
This study aims to formulate an inclusive and sustainable collaborative governance model for tourism development in the Mandalika Special Economic Zone (SEZ), Indonesia, by applying the Analytic Hierarchy Process (AHP). The research identifies five key strategic pillars—community involvement, stakeholder commitment, resource availability, capacity building, and regulatory support as the foundation for participatory governance. Drawing on relevant literature and empirical observations, the study positions community participation, particularly that of indigenous Sasak groups, as a central element in implementing community-based tourism (CBT). However, findings show that top-down policy frameworks and weak stakeholder coordination continue to marginalize local voices. The AHP method enables a structured prioritization of governance strategies, resulting in five key recommendations: (1) strengthening vocational tourism education; (2) establishing village-based multi-stakeholder forums for deliberative planning; (3) ensuring equitable infrastructure and resource access for local communities; (4) designing spatially just regulations that protect community land and cultural heritage; and (5) building an adaptive pentahelix network involving government, the private sector, academia, civil society, and media. These strategies reflect the pressing need to rebalance power asymmetries and institutionalize inclusive planning. The study contributes both a methodological framework for decision-making and a normative proposition for embedding equity and participation into tourism governance. The Mandalika case demonstrates that collaborative governance must go beyond rhetorical inclusion by transforming how decisions are made, how resources are distributed, and how local actors are empowered.